The Romanesque Sculpture at Adel Church, West Riding — A Suggested Interpretation. (1st August 2013) - Wood, Rita
Abstract : Adel church belonged to Holy Trinity Priory in York, a dependency of Marmoutier abbey, near Tours. The simple building has plentiful sculpture on corbels, doorway and gable, and chancel arch; the programme illustrates the Second Coming of Christ (outside) and the general resurrection (inside). The entrance has suffered from weathering, but is still largely legible; it includes some novelties among its standard iconography, but the chancel arch has many more. Fourth-century baptism addresses by Cyril of Jerusalem are referred to in the capitals of the chancel arch; there are newborn babies carved in the arch itself to represent those resurrected; and the character of beakheads is made clearer. It is suggested that a designer from Marmoutier and workmen from Normandy could have been involved, and that the date would be earlier than c . 1148.